Penggunaan Media Gambar untuk Menstimulus Kemampuan Bahasa Anak Usia Dini - Nugraha, Anggi Purwa; Azizah, Rifa Fauziyatul (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2025)
This study aims to determine the extent to which the use of picture media in learning can improve early childhood language skills compared to learning without picture media, and to analyze its effect on improving language skills. This study employed a quantitative approach with a One-Group Pretest-Posttest type Pre-Experimental design. The research subjects were all group A students at PAUD Sabilul Huda, totaling 17 children, with a saturated sampling technique. Data were collected through structured observation, then analyzed using descriptive statistics and a t-test for comparison. The results showed that before the application of image media, the average language ability of children was 75.71, categorized as Developing As Expected (BSH). After the application of picture media, the average increased to 85.06 with the category of Developing Very Well (BSB). Thus, the use of image media is proven to have a positive influence on stimulating the language skills of early childhood.